Vital Staining- Pivotal Role in the Field of Pathology - Nitya K; Vikram S Amberkar; Bhuvaneshwari G Nadar (Annals of Cytology and Pathology - Peertechz Publications, 2020)
A dye or stain is capable of penetrating the living cells or tissues and not inducing immediate degenerative changes. Vital stain means a stain that can be applied on a living cells without killing them. Thus these stains have been useful for both diagnostic and surgical techniques in a variety of medical specialities. As this technique is quite simple, easy to perform and cost effective, it can be useful in diagnosing any malignant changes occurring and also preventing them in a community level. Thus this vital staining can be used as an important tool in the field of diagnostic pathology. This article reviews about the various types of vital stains and its applications in the field of pathology.